Chester H. Krum, The Revised Ordinance City of St. Louis. No. 17188. Approved April 7, 1893 pg. 885, art. 4, § 1054 (1895) - (:unkn) unknown (General Publisher, 1887)
No person shall sell to any child under the age of sixteen years, without the written consent of the parents or guardian of such child, any cartridge of fixed ammunition of which any fulminate is a component part, or any gun, pistol or other mechanical contrivance arranged for the explosion of such cartridge, or of any fulminate.
--
Keywords: TRANSFER - MINORS